A Natural Deep Eutectic Solvent as an Effective Material for Dual Debridement and Antibiofilm Effects in Chronic Wound Treatment - Martinez-Gomez, F (Elsevier B.V., 2024)
In chronic wound treatment, the debridement of devitalized tissue and the eradication of the biofilm must balance aggressiveness with care to protect regenerating tissues. In this study, urea, a potent chaotropic molecule, was modulated through the formation of a Natural Deep Eutectic Solvent (NADES) with betaine to develop a new debriding material (BU) suitable for application into injured dermal tissues. To evaluate BU s debriding capacity, along with its antibiofilm effect and biocompatibility, pre-clinical to clinical methods were employed. In vitro determinations using artificial and clinical slough samples indicate that BU has a high debriding capacity. Additionally, BU s de-structuring effects lead to a strong antibiofilm capability, demonstrated by a reduced bacterial load compared to the antiseptic PHMB-Betaine or medical honey, evaluated in artificial slough and ex vivo human skin. Furthermore, BU s efficacy was evaluated in a murine model of diabetic wound, demonstrating significant effects on debriding and antibiofilm capacity, similar to those observed in PHMB-Betaine and medical honey-treated animals. Finally, BU was clinically evaluated in leg ulcers, showing superiority in reduction of bacterial load and wound area compared to honey, with no adverse effects. Thus, BU represents a simple and non-biocidal option that could contributes to chronic wound care. © 2024